Key educational and research factors affecting the future of medical education discipline in Iran: A qualitative study - Atiye Faghihi; Mohammad Hoseini Moghadam; Nikoo Yamani (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Along with the evolutions of medical sciences education, the importance of medical education discipline has gained more attention for keeping up with these evolutions. Therefore, paying attention to policymaking regarding the development of this discipline and its position in universities is very necessary. AIMS: This study has been done with the aim of investigating key educational and research factors affecting the future of medical education discipline in Iran. SETTINGS AND DESIGN: This is a qualitative study with directed content analysis approach, which has been conducted in eight medical sciences universities having medical education department (Tehran, Iran, Shahid Beheshti, Isfahan, Mashhad, Shiraz, Tabriz, and Kerman) in 2018-2019. SUBJECTS AND METHODS: A total of 25 participants (professors, students, and graduates) of medical education discipline were selected by purposeful sampling and with maximum diversity. Data were collected through semi-structured interviews. Interviews were analyzed using MAXQDA software. RESULTS: After analyzing the data, a number of 1561 initial codes were obtained, of which 914 codes were extracted after removing repetitious codes and merging similar codes. Finally, the obtained results from content analysis were classified into two main categories including key educational and research factors and ten subcategories. CONCLUSIONS: Among the most important key educational and research factors affecting the future of medical education discipline, it can be mention to the role of the discipline curriculum and need to revise it, the need to monitor the graduates and their status , globalization, the role of medical education centers and departments, and the role of theses. It is recommended that future studies investigate other key factors affecting the future of the discipline.